2020
DOI: 10.3892/etm.2020.8526
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin resistance‑associated circRNA_101237 serves as a prognostic biomarker in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of cancer-associated mortality worldwide. Despite clinical advances, the survival rate of patients with HCC remains low, as most patients are diagnosed with HCC when they are already at the advanced stage. Certain circular RNAs (circRNAs) are closely associated with the development of liver cancer. In the present study, a circRNA array was performed to screen differentially expressed circRNAs in HCC tissues. The further analysis focused on the newly identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
(26 reference statements)
1
20
0
Order By: Relevance
“…As reported by a lot of studies, there is a correlation between abnormally expressed circRNAs and clinical features, with the former possibly becoming a biomarker for NSCLC [23][24][25] . circRNA_101237, a novel identified circRNA, whose encoding gene is located at chromosome (chr) 13:26974589-26975761 and which is produced by backsplicing of exons 10, 11 and 12 of cyclin-dependent kinase (CDK) 8, has been reported to be implicated in Cisplatin resistance-associated of HCC 8 . Nevertheless, we still do not well understand how circRNA_101237 affects NSCLC as well as the potential mechanisms it holds.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by a lot of studies, there is a correlation between abnormally expressed circRNAs and clinical features, with the former possibly becoming a biomarker for NSCLC [23][24][25] . circRNA_101237, a novel identified circRNA, whose encoding gene is located at chromosome (chr) 13:26974589-26975761 and which is produced by backsplicing of exons 10, 11 and 12 of cyclin-dependent kinase (CDK) 8, has been reported to be implicated in Cisplatin resistance-associated of HCC 8 . Nevertheless, we still do not well understand how circRNA_101237 affects NSCLC as well as the potential mechanisms it holds.…”
Section: Discussionmentioning
confidence: 99%
“…For example, circRNA_101237 is a prognostic biomarker associated with resistance to cisplatin in hepatocellular carcinoma. 21 In addition, circFBXO11 regulates the progression and oxaliplatin resistance of hepatocellular carcinoma by modulating the miR‐605/FOXO3/ABCB1 axis, 22 whereas hsa_circ_0079662 induces human colon cancer cell resistance to oxaliplatin via affecting the TNF‐α pathway. 23 Sequencing studies have also found that mRNA, circRNA, and lncRNA expression profiles in extracellular vesicles derived from human serum samples offer promise as diagnostic cancer biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest was the observation that cisplatin induced expression of the circRNA. 127 hsa_circ_0027089 Microarray analysis was carried out on plasma samples from 10 patients with HBV-related HCC and 5 patients with HBV-related cirrhosis. Of the panel of up- and down-regulated circRNAs, hsa_circ_0027089 was identified as a potentially useful diagnostic marker that distinguishes HCC from cirrhosis in patients with chronic HBV infection.…”
Section: Circrnas Implicated In the Etiology Of Hepatocellular Carcinmentioning
confidence: 99%
“… 129–132 Upregulated and downregulated circRNAs were identified, then measured in patients’ samples to correlate with features of tumor cell proliferation, invasion and spread. More recently screening of RNA extracted from tumor and normal tissue using microarray analysis 119 , 124 , 125 , 127 , 128 has also been performed. These analyses were followed by verification using RT-qPCR.…”
Section: Circrnas Implicated In the Etiology Of Hepatocellular Carcinmentioning
confidence: 99%
See 1 more Smart Citation